1981
DOI: 10.1079/bjn19810089
|View full text |Cite
|
Sign up to set email alerts
|

The digestibility of amino acids in the small intestine of the sheep

Abstract: Present address: Drayton Experimental Husbandry Farm, Alcester Rd, Stratford upon Avon, Wanvickshire. 1. The digestibilities of microbial and food proteins in the small intestine were studied in three sheep fitted with reentrant cannulas in the proximal duodenum and terminal ileum.2. The quantities of microbial and food proteins at the small intestine were varied by infusion of a microbial isolate or by dietary manipulation and the balance of amino acids along the small intestine was determined. 3. A mean valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…In the ileum this fraction was only 19 to 22%) of the NAN, demonstrating the high digestibility of microbial N, on average 77%). This value is in agreement with numerous data from literature (Tas et al,1981;Storm et al, 1983;Hvelplund, 1985).…”
Section: Discussionsupporting
confidence: 93%
“…In the ileum this fraction was only 19 to 22%) of the NAN, demonstrating the high digestibility of microbial N, on average 77%). This value is in agreement with numerous data from literature (Tas et al,1981;Storm et al, 1983;Hvelplund, 1985).…”
Section: Discussionsupporting
confidence: 93%
“…Estimates of true digestibility in the small intestine for amino acid nitrogen in bacterial protein have been obtained by Tas et al (1981), Storm et al (1983) and by infusing bacterial protein into the abomasum. The values obtained varied between 0.85 and 0.87.…”
Section: Amino Acid Composition and Digestibility Of Bacterial Proteinmentioning
confidence: 99%
“…Applying regression techniques, Tas et al (1981) reported a value of 0.82 for the true digestibility of undegraded amino acids passing to the duodenum of sheep fed a diet of grass and concentrates. measu shee red the increments in protein and amino acids passing the terminal ileum when different proteins, which had previously been exposed to some degradation in the rumen, were infused into the abomasum of sheep.…”
Section: Intestinal Digestibility Of Amino Acids In Rumen Undegraded mentioning
confidence: 99%
“…While amino acid absorption in the caecum-colon is generally of minor importance (Ulyatt et al, 1975), protein degradation can be substantial if degradable protein is available in this section of the gut (Ulyatt et al, 1975;Varvikko & Vanhatalo, 1990). Recent in vivo studies have focused on digestion in the small intestine between the proximal duodenum and the terminal ileum (Tas et al, 1981;Storm et al, 1983;Hvelplund, 1985;Hvelplund, 1987). The mobile bag technique with the insertion of bags in the duodenum and faecal recovery is an alternative to in vivo methods for estimating postgastric digestion (Hvelplund, 1985;Voight et al, 1985;Varvikko & Vanhatalo, 1990;Todorov & Girginov, 1991;Hvelplund et al, 1992).…”
Section: Introductionmentioning
confidence: 99%